Principles of corporate finance - Brealey, Richard A.; Myers, Stewart C.; Allen, Franklin, 1956- (New York : McGraw-Hill Education, 2020)
"ISBN: 9781260565553 is an International Student Edition of Principles of Corporate Finance 13th Edition by: Richard A Brealey, Stewart C Myers and Franklin Allen This ISBN is Textbook only. It will not come with online access code. The content of of this title on all formats are the same. Brealey, Principles of Corporate Finance, 13e, describes the theory and practice of corporate finance" -- Amazon.
Part One. Value -- Part Two. Risk -- Part Three. Best Practices in Capital Budgeting -- Part Four. Financing Decisions and Market Efficiency -- Part Five. Payout Policy and Capital Structure -- Part Six. Options -- Part Seven. Debt Financing -- Part Eight. Risk Management -- Part Nine. Financial Planning and Working Capital Management -- Part Ten. Mergers, Corporate Control, and Governance -- Part Eleven. Conclusion.
Includes index.
BBS
Development Book Agency
Keywords: Corporations -- Finance; Business & finance